Clinical response to the CHAPRR protocol in refractory livedoid vasculopathy: a case report (Brazilian Journal of Health Research, 2024)
Introduction: Livedoid vasculopathy is a chronic and recurrent thrombo-occlusive vascular disease of the distal lower limbs and feet that can lead to the formation of ulcers. Connective tissue diseases, antiphospholipid antibody syndrome, systemic vasculitis and neoplasms may be associated. Treatment is challenging, as the pathophysiology of the lesions involves multiple mechanisms. Case report: we report the case of a middle-aged woman diagnosed with livedoid vasculopathy, a clinical condition that is difficult to manage, with remission of skin lesions after the introduction of the CHAPRR regimen (calcium channel blocker, hydroxycloquine, AAS, pentoxifylline, rivaroxaban and Rituximab). Conclusion: As it is a rare entity, there is no defined consensus on its treatment, therefore the relevance of the topic exemplified in this case report is emphasized.
Keywords: Livedoid Vasculopathy; Livedo Reticularis; Summer Ulceration; White Atrophy